Focus on gut microbes: new direction in cancer treatment - Liao, Lingshan; Zeng, Mengying; Liu, Debei; He, Yuxing; Du, Wei; Cao, Yanlin (Frontiers in Oncology, 2025)
Gut microbes are emerging as critical regulators in cancer therapy, influencing the efficacy and toxicity of radiotherapy, chemotherapy, immunotherapy, targeted therapy, Traditional Chinese Medicine, and rehabilitation interventions. Acting through metabolic reprogramming, immune modulation, DNA damage, and tumor microenvironment remodeling, specific microbial taxa and their metabolites can either enhance or hinder treatment outcomes. However, these interactions are highly context-dependent and shaped by individual factors such as diet, geography, and host immunity. While microbial interventions such as probiotics, fecal microbiota transplantation, and engineered bacteria show promise, their translation into precise and safe clinical applications remains limited by interindividual variability, regulatory hurdles, and incomplete mechanistic understanding. Future efforts should focus on defining high-evidence microbial signatures, clarifying causal mechanisms, and developing personalized microbiome-based therapeutic strategies, potentially integrated with nanotechnology. This review underscores the need for interdisciplinary approaches to harness gut microbiota as co-targets in cancer treatment.